2018
DOI: 10.1371/journal.pone.0203158
|View full text |Cite
|
Sign up to set email alerts
|

Off-label use of ceftiofur in one-day chicks triggers a short-term increase of ESBL-producing E. coli in the gut

Abstract: This trial was designed to evaluate the off-label use of ceftiofur with Marek’s vaccine in one-day-old broiler chicks, a prophylactic treatment that has been done in some commercial hatcheries, on the emergence of extended-spectrum beta-lactamase producing Escherichia coli (ESBL-E. coli). A total of 168 chicks (Cobb500®) were used in a completely randomized design. Birds were assigned to two treatments (Marek’s vaccine plus saline vs Marek’s vaccine plus ceftiofur) and six repetitions, with 14 animals each. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…These results are in accordance with previous works which reported cephalosporin-resistance in Salmonella from food-producing animals and poultry meat, since early 2000s [9,35,36]. Third-generation cephalosporin, as ceftiofur, have been frequently used in day-old chicks together with Marek's vaccine [16], and it is related to short-term antimicrobial resistance in Enterobacteriaceae [13,14].…”
Section: Antimicrobial Susceptibility Testingsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are in accordance with previous works which reported cephalosporin-resistance in Salmonella from food-producing animals and poultry meat, since early 2000s [9,35,36]. Third-generation cephalosporin, as ceftiofur, have been frequently used in day-old chicks together with Marek's vaccine [16], and it is related to short-term antimicrobial resistance in Enterobacteriaceae [13,14].…”
Section: Antimicrobial Susceptibility Testingsupporting
confidence: 92%
“…Despite that CEF is not a common cephalosporin used in human medicine, previous studies have shown a strict relationship between it and CTX resistance in Enterobacteriaceae [13,37]. We found complete agreement in that CEF and CTX resistance.…”
Section: Antimicrobial Susceptibility Testingsupporting
confidence: 70%
See 2 more Smart Citations
“…and E. coli producing bla CTX-M-variants have been detected in poultry farms environment and on the surface of flies from dairy farms, respectively [124,145]. In addition, a study has shown that the prophylactic administration of ceftiofur to one-day-old broiler chicks may be associated with early carriage of ESBL-producing E. coli in the gut of these animals [154]. Table 5 describes the source, geographic location of sampling, and bla genes found in studies that reported ESBL and pAmpC-encoding genes in food or food-producing animals in Brazil. In Salmonella, bla CTX-M-2 was identified in non-transferable and conjugative plasmids of 90 to 290 kb.…”
Section: Streptococcus Sppmentioning
confidence: 99%